Pengaruh Kualitas Pelayanan Bus Trans Sarbagita Terhadap Kepuasan Masyarakat Pengguna Jasa Transportasi di Bali (Studi Kasus: Koridor 1 dan Titik Pertemuan Koridor 1-2 Trans Sarbagita) - Rihi, Indra Alfian; Noak, Piers Andreas; -, Bandiyah (CITIZEN CHARTER, 2018)
ABSTARCT Providing value and satisfaction to consumers through the provision of quality and quality services is one of the strategies used by transportation service providers to lure customers to use public transportation services again. Good service quality isn’t only measured from the luxury of the Service Quality of the technological completeness and the physical appearance of the officer. The result of this research shows that the service quality of Bus Trans Sarbagita has positive effect on the satisfaction of the people who use the transportation service in Bali with R2 result of 0.640, which means that the satisfaction of the users of transportation service in Bali is influenced by the service quality of Trans Sarbagita Bus by 64%. The results of simple linear regression calculations show that if the quality of service increased by one percent it will result in an increase of the value of customer satisfaction of 98.6 percent. Keywords: Service Quality, Customer Satisfaction, Trans Sarbagita.